Stress intensity factor of aircraft attachment lug with cracked holes - Divya Bharathi Perumal (2016)
This project deals with the determination of stress intensity factor numerically and experimentally in order to predict the crack propagation in the attachment straight lug. The specimen was made of Aluminium alloy A17075-T651 with two symmetric quarter comer elliptical cracks placed diametrically opposite to each other around a hole. An initial elliptical part through crack was fabricated in the specimen so that the crack propagation can be predicted with the application of load. Three crack configurations were used in this work so that the propagation of crack can be compared for three different cases. Initially, the specimen was subjected to tensile loading where the load was applied for different crack configurations until it fails. This gives the ultimate tensile load with which the experiment was proceeded. A specific percentage of breaking load was used to carry out the fatigue tests with the help of marker load history. This kind of loading leaves distinct markings on the specimen surface during fracture. The striation lines correspond to the periodic amplitude load sequence. These marks were clearly captured using portable digital microscope. The pictures taken were edited using Photoshop to increase its contrast and brightness settings for an even clearer view. These marks were analysed and the crack propagation was measured. It is then analysed and data processing were carried out to obtain the results. A two dimensional through-the-thickness finite element analysis was carried out for straight lug with single crack and two symmetric cracks on the edge of a hole using ANSYS WORXBENCH 15. From the results obtained, the effect of geometry factor on the crack propagation was studied.